2018
DOI: 10.3389/fcvm.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Sharing Between Genetic and Gestational Hypoxia-Induced Cardiac Anomalies

Abstract: Background: Cardiac development is a dynamic process both temporally and spatially. These complex processes are often disturbed and lead to congenital cardiac anomalies that affect approximately 1% of live births. Disease-causing variants in several genetic loci lead to cardiac anomalies, with variants in transcription factor NKX2-5 gene being one of the largest variants known. Gestational hypoxia, such as seen in high-altitude pregnancy, has been known to affect cardiac development, yet the incidence and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 40 publications
4
13
1
Order By: Relevance
“…In this study, we analyzed coronary vessel organization in embryonic hearts exposed to continuous mild gestational hypoxia (O 2 , 14%) compared to normoxic hearts and found defective coronary vessel organization (Figure ) and a reduction in VEGF‐A mRNA and proteins (Figure 1D‐G). The E15.5 hearts with hypoxia showed a tendency for thinner compact layer, and an increase of trabecular area relative to the compact area (Figure 1B‐C), which is consistent with our previous study showing that newborn mice with gestational hypoxia develop cardiac anomalies, such as ventricular septal defects, excessive ventricular trabeculation, and irregular interventricular septum . These data suggest the link between hypoxia‐induced defective coronary vessel organization and cardiac anomalies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, we analyzed coronary vessel organization in embryonic hearts exposed to continuous mild gestational hypoxia (O 2 , 14%) compared to normoxic hearts and found defective coronary vessel organization (Figure ) and a reduction in VEGF‐A mRNA and proteins (Figure 1D‐G). The E15.5 hearts with hypoxia showed a tendency for thinner compact layer, and an increase of trabecular area relative to the compact area (Figure 1B‐C), which is consistent with our previous study showing that newborn mice with gestational hypoxia develop cardiac anomalies, such as ventricular septal defects, excessive ventricular trabeculation, and irregular interventricular septum . These data suggest the link between hypoxia‐induced defective coronary vessel organization and cardiac anomalies.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study showed that Hif1α was upregulated in E12.5 hearts under severe hypoxia (8% for 6 hours) . Under 14% chronic hypoxia starting from E10.5, however Hif1α mRNA and proteins were not upregulated in embryonic hearts either at 2 days (E12.5) or 8 days (E18.5) of exposure to hypoxia . VEGF‐A expression was most downregulated at E12.5 compared to E15.5, and was not significantly different between hypoxic and normoxic groups at E18.5 (Figure 1D).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations